Operations strategy of ahli pest to survive in competitive market - Eka Wijayanti, Arlyza; Aldianto, Leo (The Indonesian Journal of Business Administration, 2018)
Abstract. PT Pupuk Kujang is a subsidiary of PT Pupuk Indonesia (Persero), a state owned holding company focusing on production and distribution of subsidized and non-subsidized fertilizers. Issue on subsidy scheme change, natural gas price, and decreasing trend of international Urea price affecting the company’s profit. The company revenue kept increasing but its profit trend was decreasing (2012 – 2016). The company had an intention to increase its revenue through plant factory diversification plan. Grand Strategy matrix analysis was being used to conform the diversification strategy, while the value innovation of the plant factory was determined by examining parameters of design thinking perspective. Based on the company external and internal analysis, it can be concluded that the company still had its competitive advantage in the industry and diversification strategy was suitable for the company. Based on the root challenge analysis on the diversification plan, there were three aspects that can be used to define the value innovation from the plant factory development plant which are: human desirability, technology feasibility, and economic viability. The value innovation of vegetables plant factory development offered by the company should be premium vegetables products those are clean, fresh, free-pesticide, and smooth available only in premium market in Greater Jakarta and direct sales to certain business consumers. Tomatoes and some certain leafy vegetables can be applicable. The most viable technology to meet the market needs is the vegetables plant factory technology with full solar light and controlled environment system. During the implementation, the company should provide resource needed such as land, plant factory building and facilities, capital, and people. The scale and economic evaluation of the vegetables plant was profitable but still too small compared to existing revenue and profit of the company. Therefore, the vegetables plant factory development was not viable as business substitute to the existing company business in fertilizer production. Keywords: design thinking, grand strategy matrix, plant factory, premium vegetables business, value innovation